Tinjauan Literatur: Peran Brand Image dalam Membangun Loyalitas Pelanggan dan Pengaruhnya dalam Sektor Ritel - Kusumastuti, Anggit Dyah; Hidayah, Mila Nur; Kurniawan, Dony Ragata (Jurnal EMT KITA, 2025)
Brand image plays a very important role in building customer loyalty, especially in the highly competitive retail sector, and is included in the difficult business category. Brand image itself provides a positive perspective by increasing trust and also building emotions. Both between consumers who can later encourage consumer loyalty that is built automatically. The method used in this study is to look at literature by utilizing various academic journals and also official literature. For example, theses, or theses, published journals, and also academic articles obtained from Google Scholar, Siinta, and also Scopus. The results of the study indicate that there are various elements and factors that can influence brand image, which is not only a company identity but also a differentiating factor in market competition. In addition, elements that have product quality, brand reputation, and also consistent marketing strategies have become the main factors in strengthening consumer views related to image and also brands. In addition, customers feel that a brand can provide added value. So that a satisfying experience tends to be able to attract customer loyalty and also decide to use products that come from trusted places, for example, the retail in question.